2019
DOI: 10.1002/ppul.24336
|View full text |Cite
|
Sign up to set email alerts
|

Do combined upper airway cultures identify lower airway infections in children with chronic cough?

Abstract: Background Obtaining lower airway specimens is important for guiding therapy in chronic lung infection but is difficult in young children unable to expectorate. While culture‐based studies have assessed the diagnostic accuracy of nasopharyngeal or oropharyngeal specimens for identifying lower airway infection, none have used both together. We compared respiratory bacterial pathogens cultured from nasopharyngeal and oropharyngeal swabs with bronchoalveolar lavage (BAL) cultures as the “gold standard” to better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Data including patients’ demographics, duration of prior cough at bronchoscopy, household tobacco smoke exposure, diagnoses, past pneumonia history, complete blood count, airway (ie, BAL) cellularity, lower airway bacterial culture, and respiratory virus detection were extracted from the database. A positive culture in the BAL was defined as the growth of >10 4 CFU/mL of a single bacteria species . Positive culture of the three most common bacteria Haemophilus influenzae , Moraxella catarrhalis , and Streptococcus pneumonia were included as these are found in children with chronic wet cough …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data including patients’ demographics, duration of prior cough at bronchoscopy, household tobacco smoke exposure, diagnoses, past pneumonia history, complete blood count, airway (ie, BAL) cellularity, lower airway bacterial culture, and respiratory virus detection were extracted from the database. A positive culture in the BAL was defined as the growth of >10 4 CFU/mL of a single bacteria species . Positive culture of the three most common bacteria Haemophilus influenzae , Moraxella catarrhalis , and Streptococcus pneumonia were included as these are found in children with chronic wet cough …”
Section: Methodsmentioning
confidence: 99%
“…A positive culture in the BAL was defined as the growth of >10 4 CFU/mL of a single bacteria species . Positive culture of the three most common bacteria Haemophilus influenzae , Moraxella catarrhalis , and Streptococcus pneumonia were included as these are found in children with chronic wet cough …”
Section: Methodsmentioning
confidence: 99%
“…19 Although spirometry (pre-and post-ß2-agonists) is commonly performed in daily practice, literature data are lacking regarding its use in the pediatric population with chronic cough. [9][10][11][12][14][15][16][17][18][19][20][21][22][23] Nevertheless, in their multicenter study, the authors revealed that spirometry showed a sensitivity of 0.03 (95% CI: 0.01-0.06), specificity of 1.0 (95% CI: 0.89-1.00), positive PV of 1.00 (95% CI: 0.60-1.0), negative PV of 0.13 (95% CI: 0.09-0.17), positive LR infinity, and negative LR of 0.97 (95% CI: 0.95-0.95) for the specific cough all-causes. 13 Finally, only one of the studies included in our systematic review investigated the diagnostic role of fractional…”
Section: Discussionmentioning
confidence: 99%
“…18 Only one study did not make the chronic cough definition explicit. 17 More recently, according to the latest CHEST Expert Cough Panel guidelines, chronic cough has been defined as the presence of daily cough for more than 4 weeks for children aged ≤14 years. 26…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation